2003
DOI: 10.1021/ie020780f
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Generic Fluidized-Bed Reactor Model to the Fluidized-Bed Membrane Reactor Process for Steam Methane Reforming with Oxygen Input

Abstract: A generic fluidized-bed reactor model (Abba et al. Chem. Eng. Sci. 2002, 57, 4797-4807; AIChE J. 2003, in press) is adapted to evaluate the performance of a fluidized-bed membrane reactor for steam reforming with oxygen input in a large-scale unit (16 m high and 2 m wide) described by Adris and Grace (Ind. Eng. Chem. Res. 1997, 36, 4549-4556). This allows flow regimes beyond bubbling to be modeled and facilitates the treatment of the impacts of changes in volumetric flow due to variations in molar flow, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Ethane dehydrogenation -Propane dehydrogenation -Cyclohexane dehydrogenation -Ethylbenzene dehydrogenation Abdalla and Elnashaie, 1995 Water-gas shift reaction -Methane steam reforming Abba et al, 2003;Adris et al, 1991Adris et al, , 1994aAdris and Grace, 1997;Chen et al, 2003a,b,c;Elnashaie, 2004a,b, 2005a,b,c;Gobina, 2000;Grace et al, 2001;Patil et al, 2005;Prasad and Elnashaie, 2002;Rakib and Alhumaizi, 2005 Methane partial oxidation to synthesis gas Mleczko et al, 1996;Ostrowski et al, 1998aOstrowski et al, ,b, 1999 Selectivity enhancement Oxidative coupling of methane -Partial oxidation of ethane to ethene Ahchieva et al, 2005 Ethylene epoxidation -Partial oxidation of propane to propene Alonso et al, 2005 Partial oxidation of propane to acrolein -Partial oxidation of butane to maleic anhydride Alonso et al, 2001 Partial oxidation of butene to methacrolene -Partial oxidation of methanol to formaldehyde Deshmukh et al, 2005a,b,c CO hydrogenation to hydrocarbons -Oxidative dehydrogenation of ethylbenzene - 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 Year Number of publications Our paper is based on a database search for the years 1965-2005 with the software SciFinder Scholar (2004) and with keywords "Fluidized beds and membranes". The obtained number of publications per year is plotted for the past 15 years in Fig.…”
Section: Conversion Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethane dehydrogenation -Propane dehydrogenation -Cyclohexane dehydrogenation -Ethylbenzene dehydrogenation Abdalla and Elnashaie, 1995 Water-gas shift reaction -Methane steam reforming Abba et al, 2003;Adris et al, 1991Adris et al, , 1994aAdris and Grace, 1997;Chen et al, 2003a,b,c;Elnashaie, 2004a,b, 2005a,b,c;Gobina, 2000;Grace et al, 2001;Patil et al, 2005;Prasad and Elnashaie, 2002;Rakib and Alhumaizi, 2005 Methane partial oxidation to synthesis gas Mleczko et al, 1996;Ostrowski et al, 1998aOstrowski et al, ,b, 1999 Selectivity enhancement Oxidative coupling of methane -Partial oxidation of ethane to ethene Ahchieva et al, 2005 Ethylene epoxidation -Partial oxidation of propane to propene Alonso et al, 2005 Partial oxidation of propane to acrolein -Partial oxidation of butane to maleic anhydride Alonso et al, 2001 Partial oxidation of butene to methacrolene -Partial oxidation of methanol to formaldehyde Deshmukh et al, 2005a,b,c CO hydrogenation to hydrocarbons -Oxidative dehydrogenation of ethylbenzene - 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 Year Number of publications Our paper is based on a database search for the years 1965-2005 with the software SciFinder Scholar (2004) and with keywords "Fluidized beds and membranes". The obtained number of publications per year is plotted for the past 15 years in Fig.…”
Section: Conversion Enhancementmentioning
confidence: 99%
“…Adris et al (1991Adris et al ( , 1994a demonstrated that for steam reforming of natural gas the thermodynamic equilibrium restrictions can be overcome by in situ separation and removal of hydrogen via perm-selective thin-walled palladiumbased membranes leading to increased synthesis gas yields in comparison to the industrial fixed bed steam reformer. Subsequently, Grace and co-workers (Roy et al, 1999;Grace et al, 2001;Abba et al, 2003) and Elnashaie and co-workers (Chen et al, 2003a,b,c;Prasad and Elnashaie, 2002) added oxygen into these steam reforming reactors for in situ generation of heat by partial oxidation of methane to supply the energy for the endothermic reforming reaction. Prasad and Elnashaie (2002) used CO 2 sequestration using CO 2 -lime reaction to assist/replace the hydrogen perm-selective membranes.…”
Section: Equilibrium Limited Reactions (Conversion Enhancement)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reactor models (e.g. Abba et al, 2003;Chen et al, 2003;Dogan et al, 2003;Grace et al, 2001;Patil et al, 2007) have also been developed to simulate FBMR processes. Experimental studies in a commercial FBMR unit were reported by Chen et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…One option is to employ fluidized-beds to augment mass and heat transfer (Chen, 2002;Abba et al, 2003;Chen and Elnashaie, 2004;Boyd et al, 2005;Grace et al, 2005;Patil et al, 2005Patil et al, , 2006Patil et al, , 2007Rakib and Alhumaizi, 2005;Abashar et al, 2007;Deshmukh et al, 2007). Another is to introduce membrane separation.…”
Section: Introductionmentioning
confidence: 99%